The measurement of residential sprawl in the Johannesburg Metropolitan Area - Sieg, SM; Landre, M (Town and Regional Planning, 1991)
Residential development in large parts of the Johannesburg metropolitan area is characterized by sprawl conditions. A simulation model was utilized to indicate the extent of future sprawl. Multiple regression and Monte Carlo simulation were used to fore cast residential growth to the year 2005. A sprawl index was developed to measure and compare sprawl situations under alternative planning strategies. This index formulates that sprawl is dependent on distance from the built boundary, distance to the dominant work place and dwelling unit density. Simulations show that sprawl will decrease when the overall density is increased, development is concentrated along major transport corridors and incentives are used to attract development to slowly expanding areas.